Bubble annular photoeletrocatalytic reactor with TiO2 nanotubes arrays applied in the textile wastewater - Cardoso, Juliano Carvalho [UNESP]; Lucchiari, Natália; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2015)
This study proposed a simple and effective annular bubble photoreactor using an array of TiO2 nanotubes (NTs) prepared in situ by an anodisation process and used as photoanodes. The method is based on photoelectrocatalytic oxidation of the industrial textile wastewater (pH 7.83; conductivity 9.96 mS cm-1; total dissolved solids 4.97 ppt; turbidity 0.04 NTU; colour 1146 mg/Pt; total organic carbon 5680 ppm and inorganic carbon 408.1 ppm) operating as follows: original pH of the effluent corrected to 2; current density of 9 mA cm-2, commercial Hg high press lamp (250 W) irradiating at UV and visible region, and air bubble stirring of 700 mL min-1. Using these optimised conditions, it was possible to obtain 90% colour removal (initial = 1.146 mg Pt), 66% COD reduction (initial = 5680 ppm) and 70% TOC removal after 3 h of treatment, reaching acceptable physicochemical properties for discharge.
Keywords: Bubble annular photoreactor; Photoelectrocatalytic oxidation of textile wastewater; Textile effluent treatment; TiO2 nanotubes arrays